Indirect immunofluorescence antibodies to Legionella pneumophila: frequency in a rural community. - Helms, C M (1980)
The background prevalence of indirect immunofluorescence antibody to Legionella pneumophila in a rural community was determined by testing sera from 517 volunteers. The upper limit of normal antibody titer was found to be 1:64 with L. pneumophila serogroup 1 (Philadelphia 1) used as antigen. High titers (greater than or equal to 1:128) were found in 13.2% of the sera and occurred with similar frequencies in males and females. In individuals 40 years of age and older, however, high titers were 2.7 times as prevalent in males as females.